Jerusalem artichoke tuber flour as a wheat flour substitute for biscuit elaboration. (July 2019) - Díaz, Andrea; Bomben, Renata; Dini, Cecilia; Viña, Sonia Z.; García, María A.; Ponzi, Marta; Comelli, Nora
Abstract: Jerusalem artichoke produces underground tubers which accumulate fructans, mainly inulin, which can be regarded as functional dietary fiber. In the present work, flour from Jerusalem artichoke (JA) was obtained and this product resulted in a source of inulin (48.97 ± 3.40 g/100 g dry base, db) and phenolic compounds (272 ± 22 mg gallic acid equivalents/100 g). Total protein and fat content in JA flour was 4.27 ± 0.02 and 0.53 ± 0.01 g/100 g db, respectively. The glass transition temperature (Tg) of the flour, which is a critical parameter that determines the storage temperature of this product, was determined by thermal analysis. The flour remained thermally stable up to 190 °C, which limits the baking temperature. Biscuits were formulated from a mixture of flours from wheat (WF), amaranth (AF) and JA (JAF). The baking condition (150 °C, 15 min) was selected based on the color and texture attributes of the baked products. The percentage of substitution of the wheat flour was limited by the sensory characteristics of the biscuits obtained. The formulation containing 8% AF, 17% JAF and 75% WF exhibited the higher rate of acceptance, resulting a healthier alternative, with lower energy content than traditional wheat flour-based biscuits. Highlights: Jerusalem artichoke (JA) flour is a source of inulin and phenolic compounds. Biscuits were obtained by partial substitution of wheat with JA and amaranth flour. Biscuits sensory characteristics and quality attributes were evaluated.